Dynamical Analysis of New Fractional Order ZIKV Model with Nonlinear Incidence Rate - Nurul Anggraeni Hidayati (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
The ZIKV model provided is derived by adapting the model proposed by Hidayati2021. This study enhances the existing model by transforming it into a fractional-order ZIKV model with a nonlinear incidence rate. The model's equilibrium points are identified, and the stability conditions for each point are evaluated using the Routh-Hurwitz criterion. A numerical simulation is performed to validate the stability study results. Numerical simulations further demonstrate the impact of the order α on the stability of the equilibrium point inside the model.